Psychosocial Experiences That Support Positive Self-Concept in Children with Cleft Lip and/or Palate Adopted from China - (:unkn) unknown (My University, 2020)
Cleft lip and/or palate (CL/P) is the most common birth defect occurring in the United States (Parker et al., 2010). Children diagnosed with CL/P and their families face significant burden associated with frequent and costly medical appointments (Tolarova, Al-Kharafi, & Tolar, 2018). Children with CL/P are at higher risk for associated genetic conditions, neuropsychological correlates (Conrad, Richman, Nopoulos, & Dailey, 2009), and psychosocial stressors such as social difficulties and internalizing symptoms (Richman, McCoy, Conrad, & Nopoulos, 2012). Self-concept and other self-perceptions have been found to mediate the relationship between negative events and internalizing symptoms (Feragen, Borge, & Rumsey, 2009; Rumsey & Harcourt, 2005). Therefore, further research into experiences that support self-concept in children with CL/P will contribute to an understanding of protective factors for psychosocial difficulties. Children adopted from China who have CL/P often experience different clinical pathways for medical treatment such as receiving corrective surgeries later than non- international adoptees (Swanson et al., 2014). In addition, children adopted from China with cleft lip and palate may face additional challenges related to acculturation, discrimination, or bullying. The existing research offers very little information on the unique challenges and strengths of children adopted from China with CL/P. Thus, it is unknown if children adopted from China with CL/P have different strategies for development and maintenance of positive self-concept. ii Previous research has not focused on the perspectives of young children, particularly from a qualitative viewpoint (Sharif, Callery, & Tierney, 2013). The present study adds to the psychosocial literature base of children with CL/P who have been adopted from China by qualitatively exploring child experiences with a strengths-based approach, consistent with the evolving trend in the literature (Stock & Feragen, 2016). The present study utilizes Interpretive Phenomenological Analysis (IPA) to understand social, family, personal, and healthcare factors that support positive self-concept in children and adolescents with cleft lip and palate adopted from China.
Keywords: cleft lip and palate; craniofacial; international adoption; pediatric psychology